Manajemen Konflik Pada Sekolah Tinggi Ilmu Kesehatan Bethesda Tomohon - Nelwan, Julita Inggrinne; Timpal, Cornelia (El-Idare, 2023)
Implicitly conflict cannot be generalized as something that is harmful or beneficial. Conflict can improve the performance and productivity of an organization, if the leader of the organization has the ability to manage conflict. The purpose of this research is to find out how institutions manage conflicts that occur between students, students and lecturers, between fellow lecturers, lecturers and leaders. The method used in this study is a qualitative naturalistic method. The research procedures with procedures are the orientation stage, the exploration stage, and the member check stage. Data collection techniques used are observation, interviews, field notes, and documentation. Data analysis was carried out simultaneously with the data collection process. The results of the research show that the conflicts that occurred at the Bethesda Tomohon High School of Health Sciences involved: (a) student-student conflicts, (b) lecturers and lecturers or administrative staff, (c) lecturers and students, and (d) directors and lecturers.